Inter-pregnancy interval and associated factors among parous women in neighboring low-land ecologies of arsi & east shoa zone, southeast Ethiopia: a community-based cross-sectional study - Gebi Husein Jima; Regien Biesma; Tegbar Yigzaw Sendekie; Jelle Stekelenburg (Contraception and Reproductive Medicine)
Abstract Background The World Health Organization (WHO) recommends an interval of at least 24 months from the date of a live birth to the conception of the next pregnancy in order to reduce the risk of adverse maternal, perinatal, and infant outcomes. There is limited data about the implementation of this recommendation and its contributing factors in low-land ecologies in Oromia, which is the biggest regional state in Ethiopia. Objective To assess the inter-pregnancy interval and determine associated factors among parous women in selected low-land districts of Arsi and East Shoa Zone. Methods A community-based cross-sectional study was conducted. Data were collected from a random sample of 563 women using a structured, pre-tested questionnaire. Bivariate and multivariate analysis was conducted, and the magnitude of the association between the inter-pregnancy interval and explanatory variables was measured using adjusted odds ratios and their 95% confidence intervals. Results The rate of short inter-pregnancy interval (SIPI) was 28.20% (95% CI: 24.48-31.92%). After multiple logistic regression analysis, women with primary education, women who believed that low contraceptive use contributed to SIPI, women who thought SIPI could impact small for gestational age, and women who thought SIPI could affect birth defects had a lower chance of having SIPI; aOR of 0.54 (95% CI: 0.30–0.79), 0.33 (95% CI: 0.16–0.68), 0.57 (95% CI: 0.32–0.94 and 0.63 (95% CI: 0.40–0.96), respectively. Conclusion Women with primary educational status, those who had better contraception literacy, and who knew about the adverse maternal and perinatal health impacts of SIPI were more likely to follow the recommended inter-pregnancy interval. Improving women’s family planning literacy is crucial to lowering the rate of SIPI currently observed in the study area.